Zastosowanie metody DEA do analizy i oceny banków - Białas, Piotr (Using DEA Method to Analyze and Estimate Banks, 2007)
In this work I presented examples of adopting DEA method to analyze the efficiency of Polish banks. Data from thirty seven Polish banks were used as a basis for this research. The intermediating approach was used to qualify inputs and outputs. Received results of effectiveness were analyzed by using Malmquist productivity index and also: benchmarking and modified BCG array, which is the only portfolio method.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1167, s. 21-32